ҲӘЗИРГИ ПОВЕСТЬЛЕРДЕ МИЛЛИЙЛИГИМИЗ ТЫМСАЛЫ МУҲАДДЕС ИНСАНЛАР КЕЛБЕТИ (Ш.Уснатдинов повестьлери мысалында) - Алламбергенов, К.; Сагидуллаева, З.Б. (SCIENCE and SOCIETY, 2019)
The object of the article is the stories «Whom it’s late, whom it’s a dawn», «The last hunter» by the famous writer-publicisth Sh.Usnatdinov. There have been analyzed haw the writer entered the Karakalpak prose through the artistic publicistic school, the author’s individual ways of deseription, artistic search and shill in the creation of heroes’ images.
Keywords: publicistics; artistic literature; publicistic prose; modern main stories; direction in the development of Karakalpak stories; stories by Sh.Usnatdinov «Whom it’s late, whom it’s a dawn», «The last hunter»